From unipolarity to multipolarity: drivers of American hegemony decline - امحمد الورفلي مبروكة (Dirasat in Economics and Business, 2026)
A new world order is in the making. It has been argued that the hegemony of the United States and power advantage are shrinking in the face of rising challengers, and that the twenty fist century will not be an American century. China is poised to become a superpower in world politics. By all yardsticks, it is a dominant regional power in Asia, whether in economics, military or soft power. In some decades to come, China would be able to challenge the U.S. primacy. By looking at China’s economic growth, its military modernization programme, and its increasing soft power tactics in Asia and around the world, China‘s ongoing rise will be a significant, if not defining, factor in shaping the international system as well as the direction of U.S. foreign and security policies